Future Challenges of Quantum Optics: Research for Improved Energy Efficiency - Wolnough Cale; Lie Jie; Woolnough Cale (Journal of Tecnologia Quantica, 2024)
In the midst of the increasing need for efficient and sustainable energy, Quantum Optics has shown great potential in the energy technology revolution. These technological advances provide opportunities to address some of the most pressing challenges facing the energy sector today, including the need for cleaner and more efficient energy sources. However, there are still obstacles in the practical application of Quantum Optics-based technologies, especially in the context of energy efficiency. This research aims to identify and analyze the challenges that exist in the development and application of Quantum Optics in the energy sector, as well as proposing innovative solutions to increase energy efficiency. The main focus is on improving the efficiency of energy use in photovoltaic systems and energy storage systems. The method used in this research includes theoretical and experimental analysis. The theoretical approach involves using mathematical models and computer simulations to predict the behavior and capabilities of systems using Quantum Optics technology. Meanwhile, the experimental approach consists in testing device prototypes built on the principles of Quantum Optics to verify theoretical predictions and assess their effectiveness in practical applications. The research results show that with modifications to the design and materials, the energy conversion efficiency in photovoltaic systems can be increased by up to 20%. Additionally, the use of new materials in energy storage systems shows an increase in storage capacity of up to 25% compared to current technology. The conclusions of this study confirm that Quantum Optics has great potential to improve energy efficiency in various applications. By continuing to drive innovation in design and materials, and overcome implementation barriers, Quantum Optics can play a key role in meeting the global need for cleaner, more efficient energy in the future.